Implementasi Algoritma Knuth-Morris-Pratt dalam Fitur Pencarian Pengarsipan Dokumen Berbasis Web (Studi Kasus: Vitech Asia Group, Jakarta) - Aji Gunawan; Dimas Abisono Punkastyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The process of searching for an archival document in the administrative division at Vitech Asia Group still uses a simple and manual system, namely after the document is printed to be further managed in accordance with existing document control procedures, the archival document is stored in a cabinet or filing place. The documents managed will continue to grow over time so that storing documents manually will certainly make it difficult for admin staff when looking for documents that are needed, making work ineffective and efficient. In order for operational activities to run effectively, a computerized archive search system is needed to integrate archival data in one integrated database so that the search for a document archive can be carried out more effectively, quickly, precisely and efficiently. In this study, we will implement the knuth-morris pratt algorithm in the design of a web-based archive search system using a system development model, namely the waterfall model. The results of this study are in the form of an archive search system, with this system, document search activities become more effective, fast, precise and efficient, where this is evidenced by the results of user interviews, which previously took more than 5 minutes to search for an archive document to be ± 1 minute using a search system that has been built.